Konsep Belajar dalam Perpsektif Tafsir Al-Quran: Kajian Qs. al-‘Alaq (96): 1-5 - Sarkowi Sarkowi (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2020)
This article discusses the study of the interpretation of al-Quran 'surah al-laAlaq (96): 1-5. The results of the study concluded that the need to learn and develop science towards self-approach to God in order to achieve happiness both in the world and the hereafter later. So, if examined deeply, it will produce principles to build the concept of learning that is qualified with religious and humanistic contents. So that, the results of learning are oriented to get human happiness both in the world and in the hereafter without disregarding their nature and potential, to arouse the awareness of students cognitivly, affectivly, and psychomotoricly. Keyword : Concept, Learning, Interpretation Of Al-Quran 'Surah Al-alaq 1-5